2008
DOI: 10.1161/hypertensionaha.108.120881
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in Response to Chronic Reductions in Uterine Perfusion in Pregnant Rats

Abstract: Abstract-Reductions in uterine perfusion pressure (RUPP) in pregnant rats is associated with increased tumor necrosis factor-␣ (TNF-␣). This study was designed to determine the role of endogenous TNF-␣ in mediating changes in arterial pressure and endothelin-1 (ET-1) in RUPP rats. To achieve this goal we examined the effect of RUPP in the presence and absence of a TNF-␣-soluble receptor, etanerecept (0.4 mg/kg). Mean arterial pressure increased from 102Ϯ1 mm Hg in normal pregnant (NP) rats to 134Ϯ3 mm Hg (PϽ0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
163
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(176 citation statements)
references
References 30 publications
13
163
0
Order By: Relevance
“…Exaggerated inflammatory responses were believed to be a significant pathophysiological event during preeclampsia (25). Several biochemical parameters indicate that endothelial dysfunction is related to the inflammatory response in preeclampsia, such as elevated serum cellular fibronectin, endothelial adhesion molecules P-selectin, the intercellular adhesion molecule, the vascular cell adhesion molecule, and the platelet endothelial cell adhesion molecule levels (2,19,21,31,33). A previous study reported that the pro-inflammatory cytokines increased significantly in preeclamptic women compared to women with normal pregnancies at sea level (28).…”
Section: Discussionmentioning
confidence: 99%
“…Exaggerated inflammatory responses were believed to be a significant pathophysiological event during preeclampsia (25). Several biochemical parameters indicate that endothelial dysfunction is related to the inflammatory response in preeclampsia, such as elevated serum cellular fibronectin, endothelial adhesion molecules P-selectin, the intercellular adhesion molecule, the vascular cell adhesion molecule, and the platelet endothelial cell adhesion molecule levels (2,19,21,31,33). A previous study reported that the pro-inflammatory cytokines increased significantly in preeclamptic women compared to women with normal pregnancies at sea level (28).…”
Section: Discussionmentioning
confidence: 99%
“…16 The increase in blood pressure observed in C1q Ϫ/Ϫ ϫC1q Ϫ/Ϫ mice, although significant when compared with control matings, is moderate. Other important factors that can increase blood pressure in pregnant mice and, thus, have been related to PE, like endothelin 1 34 or angiotensin receptor agonistic autoantibodies, 35 should be studied in this model.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the increase in TNF production following hypertonic NaCl intake was restricted to the kidney as increases in plasma levels of TNF are generally observed in conditions where the proinflammatory actions of this cytokine contribute to the progression of pathological dysfunction. For instance, increases in plasma TNF levels are observed in pregnancy-induced hypertension and following administration of a high-salt diet to salt-sensitive Dahl-SS rats (21,34). In contrast, TNF does not increase blood pressure in normal rats and administration of 1% NaCl in the drinking water for 7 days was not associated with an increase in blood pressure (24,26).…”
Section: Discussionmentioning
confidence: 99%